Esclaves et affranchis chez les Voconces au Haut-Empire : l’apport des inscriptions - Marianne Béraud; Nicolas Mathieu; Bernard Rémy (Gallia)
Sixty-seven inscriptions have been recorded (42 epitaphs, 21 dedications to deities and 4 varied texts) concerning slaves and freedmen and women. Outside the Collegium venatorum at Deensium 92 individuals have been numbered, or at least probably (64 men, 26 women and 2 anonymous of undetermined sex). There were 23 individual slaves (17 men and 6 women), 69 were freedslaves (47 men, 20 women and 2 anonymous of undetermined sex) – among them 58 freedslaves of Roman citizens (43 men, 15 women) and 11 freedslaves of peregrines (4 men, 5 women and the 2 anonymous). We have in this paper successively studied the documents, the chronological and geographical distribution, the designation, status and functions, the private life, relationship with the master/mistress or patronus/-a, the religious behaviour and taking part to the civic life of slaves and freedslaves of Roman citizens and of peregrines.